DEVELOPING SPEAKING COMPETENCE THROUGH INTERACTION-BASED LEARNING (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article investigates the methodological significance of interaction-based learning in developing speaking competence in English language teaching. The study highlights the role of learner interaction in fostering communicative ability, fluency, accuracy, and confidence in oral communication. Based on theoretical analysis and classroom practices, the article demonstrates that interaction-based learning creates a learner-centered environment that promotes meaningful communication and active language use. The findings suggest that interaction-based learning is an effective pedagogical approach for enhancing students’ speaking competence in modern English language classrooms.